PELAKSANAAN SUPERVISI AKADEMIK DALAM UPAYA MENINGKATKAN KINERJA GURU DI SMK N 1 MEMPAWAH HILIR - Soni Miftahudin; Maswardi M Amin; Sukmawati Sukmawati (Universitas Tanjungpura, 2019)
Abstract This study aims to discription of implementation supervision academic by headmaster to improve teaching teacher performance at SMK N 1 Mempawah Hilir, Mempawah Regency with aspects ( 1 ) Planning of Academic Supervision ( 2 ) Implementation of Academic Supervision ( 3 ) Evaluation of Academic Supervision and ( 4 ) Follow Up of Academic Supervision. This research is qualitative methods. This study uses Miles and Huberman data analysis techniques. Source of data is comprised prinsipal, assistant prinsipal, teacher. The data collection procedures, in-depth interviews, and documentation. Checking the validty of the findings made by the used is qualitative analysis is to describe and interpret the data. Results of the discussion as follows : ( 1 ) Planning supervision academic form of academic supervision program formulate initial step is to form the supervisory team consist principal, senior teacher, and Head of competency departement. ( 2 ) Implementation of academic supervision, principal provide an assesment of teachers through class visit, namely pre class visit, class visit, and post class visit. ( 3 ) Evaluation of academic supervision as evaluate the prinsipal with the resume result of evaluation, and the result are communicated with supervised teachers. Communication is done two direction, those are the supervisor convey the results of supervision and the teacher ( 4 ) Follow up of academic supervision is to be done by principal after discuss the result of evaluation with the supervision teams and then give the punishment, reinforcment, and reward process.Keywords :Supervision of Academic School, Teacher Performance